Pengaruh Influencer pada Platform Tiktok terhadap Brand Awareness dan Purchase Intention pada cafe Monsieur Spoon di Kota Surabaya - Liem, Keisha; Sandjaja, Beatrice Frederica; Wijaya, Verina (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the influence of influencers on the TikTok platform on brand awareness and purchase intention at Monsieur Spoon cafe in Surabaya. Additionally, this study examines the role of brand awareness as a mediating variable in the relationship between TikTok influencers and purchase intention. The research method used is quantitative with a survey approach, where data was collected through questionnaires distributed to Monsieur Spoon cafe consumers who were the target of promotional content from influencers on TikTok. A total of 180 respondents participated in the survey. The results show that influencers on the TikTok platform significantly affect brand awareness and purchase intention. Furthermore, brand awareness also has a positive impact on purchase intention. The findings also indicate that brand awareness plays a role as a mediator in the relationship between TikTok influencers and purchase intention. These results have implications for business owners in the culinary industry, particularly Monsieur Spoon cafe, to further leverage digital marketing strategies through influencers on TikTok to enhance brand awareness and purchase intention among consumers. Keywords: TikTok influencers, brand awareness, purchase intention, cafe, digital marketing